Early nutritional intake influences the serum levels of nerve growth factor (NGF) and brain-derived neurotrophic factor in preterm newborns - De Nardo, Maria Chiara; Petrella, Carla; Di Chiara, Maria; Di Mario, Chiara; Deli, Giorgia; Travaglia, Elisa; Baldini, Laura; Russo, Alessia; Parisi, Pasquale; Fiore, Marco; Terrin, Gianluca (Frontiers in Neurology, 2022)
Introduction Parenteral nutrition (PN) may have detrimental effects on neurodevelopment in preterm newborns. Moreover, enteral nutrition (EN) seems to be protective. To understand the mechanisms of how neurological development can be influenced by the route of administration of nutritional intake, we investigated the relationship between the serum levels of the nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) and nutritional intake received in early life by preterm newborns. Materials and methods Specimens of blood were obtained at 28 days of life (DOL) for NGF/BDNF determination in neonates <32 weeks of gestation and/or with birth weight <1,500 g, consecutively observed in the neonatal intensive care unit. We analyzed the relation between amino acid content and energy intake and NGF/BDNF measurements at 28 DOL. PN protein intake was referred to as the total amounts of amino acid intake received daily. Results We enrolled 20 newborns (gestational age 30.45 ± 1.76 weeks, birth weight 1,340 ± 352.63 g). Serum NGF value at 28 DOL was positively correlated with enteral protein and energy intake (r = 0.767; r = 0.746, p < 0.001), whereas, negatively correlated with parenteral amino acid and energy intake (r = −0.652, p < 0.001; r = −0.466, p < 0.05). Similar significant correlations were described between BDNF level at 28 DOL and enteral energy intake (r = 0.493, p < 0.05). Multivariate regression analysis showed that NGF level at 28 DOL depends on enteral protein and energy intake administrated in the 1st week of life. Conclusion Neurotrophin values varied according to the route of nutrition administration in preterm newborns. NGF/BDNF serum levels are influenced positively and negatively by EN and PN, respectively.